Climate change on Twitter: topics, communities and conversations about the 2013 IPCC report - Pearce, Warren; Holmberg, Kim; Hellsten, Iina; Nerlich, Brigitte (Public Library of Science, 2013)
In September 2013 the Intergovernmental Panel on Climate Change published its first comprehensive assessment of physical climate science in six years, constituting a critical event in the societal debate about climate change. This paper analyses the nature of this debate in one public forum: Twitter. Using webometric methods, tweets were analyzed to discover the hashtags used when people tweeted about the IPCC report, and how Twitter users formed communities around their conversational connections. In short, the paper presents the topics and tweeters at this particular moment in the climate debate. The most used hashtags related to themes of science, geographical location and social issues connected to climate change. Particularly noteworthy were tweets connected to Australian politics, US politics, geoengineering and fracking. Three communities of Twitter users were identified. Researcher coding of Twitter users showed how these varied according to geographical location and whether users were convinced or critical of climate science or policy in their Twitter usage. Overall, users were most likely to converse with users holding similar views. However, two communities displayed significant links between climate convinced and critical users, suggesting that those engaged in the climate debate were exposed to views contrasting with their own.